Covalent Networking of a Conjugated‐Polymer Photocatalyst to Promote Exciton Diffusion in the Aqueous Phase for Efficient Hydrogen Production. Issue 4 (6th March 2022) - An, Sanghyeok; Hassan, Syed Zahid; Jung, Jin‐Woo; Cha, Hyojung; Cho, Chang‐Hee; Chung, Dae Sung
Abstract: A conjugated polymer particle in an aqueous phase is covalently networked in 3D by crosslinking with azide groups, leading to significantly enhanced activity—a high photocatalytic H2 evolution rate (11 024 µmol g −1 h −1 (λ > 420 nm)) and a high apparent quantum yield (up to 0.8%). The reaction between the photoactive azide and the alkyl chains of the conjugated polymer provides more intact intermolecular polymeric interactions in the colloidal state, thus preventing physical swelling and inhibiting the recombination of photoproduced carriers. The covalent network efficiently promotes exciton diffusion, which greatly facilitates charge separation and transfer. The azide photo‐crosslinking also leads to more compact and better‐packed nanoparticles in the aqueous phase and efficient transfer of excitons to the outer surface of the nanoparticles, where photocatalytic reactions occur. These results show that photo‐crosslinking can suppress the adverse effects of alkyl chains which inhibit photocatalytic performance. Therefore, covalent crosslinking is a promising strategy for the development of solar and hydrogen energy. Abstract : Using an additive containing an azide group during the synthesis of photocatalytic organic polymer nanoparticles for hydrogen production results in a 3D covalent network that facilitates exciton diffusion and charge separation while reducing physical swelling. The hydrogen‐evolution rate is dramatically improved, suggesting that nitrene crosslinking holds promise for solar hydrogen‐generation development.